A Study on The Reality of e-Learning for Chemistry Students During The COVID-19 Pandemic - Wedad H Al-Dahhan; Khalid Zainulabdeen; Emad Yousif; Ahmed Abdulameir Al-Amiery; Muna Bufaroosha (Chemistry Education Department, 2023)
In a survey conducted by the Department of Chemistry on the reality of e-learning, which became widespread in most international universities during the COVID-19 pandemic in 2020, up to 50 students participated to express their thoughts and confirm observations. This survey was crucial in determining the importance of e-learning for the continuity of education and its potential drawbacks. The students’ opinions were collected using specific questions designed for a questionnaire. The survey's key findings can be summarized as follows: Both students and teaching staff played pivotal roles in the success of e-learning. Additionally, the availability of logistical tools and infrastructure that facilitated communication between students and lecturers proved vital to the effectiveness of online learning.